Design of Bifunctional Nb/V Interfaces for Improving Reversible Hydrogen Storage Performance of MgH2. Issue 10 (11th October 2022) - Meng, Yang; Ju, Shunlong; Chen, Wei; Chen, Xiaowei; Xia, Guanglin; Sun, Dalin; Yu, Xuebin
Abstract : Solid‐State Hydrogen Storage In article number 2200119, Xuebin Yu, Guanglin Xia, and co‐workers realized uniform formation of Nb/V interfaces based on a molecular scale to promote H2 storage performance of MgH2 . The onset H2 desorption temperature of MgH2 of 165 °C and the reversible hydrogenation of Mg at room temperature could be realized.